Investigating the Impact of Information Asymmetry on Unexpected Audit Fees in the Tehran Stock Exchange - Meisam Jafaripour; Mohammad Banafi; Somayeh Mousavi (International Journal of Management, Accounting and Economics, 2025)
The purpose of this research is to investigate the determinants of information asymmetry on unexpected audit fees in companies listed on the Tehran Stock Exchange. The current research is applied and has causal correlation (post-event) from the methodological point of view. The statistical population of this research include all the companies admitted to the Tehran Stock Exchange. 101 companies were selected as the research sample by using the systematic elimination sampling method, and were studied in the 10-year period between 2012 and 2022, and finally 1010 observations were selected and studied as the final screened samples. In the present study, generalized square regression test or ordinary square regression test was used to reject or not reject the hypotheses. The results of the research hypothesis test showed that information asymmetry has a direct and significant effects on the auditor's unexpected fee. This means that with the increase of information asymmetry, the auditor's unexpected fee also increases and vice versa. in fact, with the increase information asymmetry in the market, which is the result of low quality financial reports and indicates high risk in providing financial information by companies and managers to the capital market, Unexpected audit fees have increased.